Does digital influencer endorsement contribute to building consumers' attitude toward digital advertising during COVID-19 pandemic? mediating role of brand attitude - Ignatius Enda Panggati; Sasmoko; Boto Simatupang; Sri Bramantoro Abdinagoro (Cogent Business & Management, 2023)
The COVID-19 pandemic is changing consumer behaviour, where consumers are shifting their activities toward digital activities. One of the popular advertising media among digital natives during the COVID-19 pandemic is digital influencers. Brands and marketers should use digital advertising and digital influencer in their digital advertising strategy to adapt to consumer behaviour changes during the COVID-19 pandemic. This study fills the gap in the advertising literature by proposing trust in digital influencers as a predictor for consumers' attitudes toward digital advertising and evaluating brand attitude as mediating variable between consumers' attitudes toward digital advertising and purchase intention. The data was collected through an online survey, and there were 461 respondents in Indonesia. Smart Partial Least Square was used to analyze, test, and validate the collected data. The result showed that trust in digital influencers, entertainment, information, and personalization directly influence consumers' attitude toward digital advertising, and brand attitude has a positive and significant influence as a mediating variable between consumers' attitude toward digital advertising and purchase intention. This study also discusses theoretical and managerial implications on how brands, marketers, and agencies can effectively use digital advertising and influencers.
Keywords: 650; digital advertising; digital influencer; entertainment; informative; personalization; trust in digital influencer